ANALISIS KEBIJAKAN OPTIMALISASI UTILISASI SUMBER DAYA MANUSIA DAN FASILITAS RISET NASIONAL - Edy Suandi Hamid; Chairil Anwar (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
This examination intend to know and analyses utilization investment research rate by research agency in coordination with Ministry of Research and Technology (KRT), and analyze ways and efforts to increase utilization of government investment in research field and reduces technical mistakes. Research conduct in BPPT, BAT AN, and LIPI, This research is a policy research with using normative - qualitative approachFrom research finding that, quantitatively human resources in non governmental department (LPND) having unbalanced ratio problem based on its functional position, especially in researcher category and non researcher. Quantitatively growth rate of research unmatched with retirement rate, resulted changing age structure tend to older age.Size limitation and lack of available data about utilization research facilities still not solved completely. Based on evaluation made by KRT, in macro, set up of condition and usage facilities lie near 50% to 75%. However, research facilities administrator still not satisfied yet with utilization of research facilities they managed. Other research facilities problems are slow supply, limited maintenance fund and lack of available spare parts.